Pengaruh Komunikasi Interpersonal Infrastructure Support Pt Profescipta Wahanatehnik Terhadap Kepuasan Klien - Ari Erlangga Satria Putra; Silvina Mayasari; Sari Ekowati Hadi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
Interpersonal communication plays a vital role in determining the success of managed service delivery, particularly in information technology-based companies. This study investigates how the interpersonal communication practices of Infrastructure Support at PT Profescipta WahanaTehnik influence client satisfaction across various service touchpoints. Employing a quantitative descriptive approach, the research was conducted through a survey using a structured questionnaire distributed to 54 employees across five active client organizations of the company. The collected data were analyzed using several statistical tests, including validity and reliability tests, simple linear regression analysis, t-test (partial), and coefficient of determination (R²). The findings demonstrate that interpersonal communication has a positive and significant effect on client satisfaction, as reflected in a t-value of 10.278 > t-table value of 2.007 and a significance level of 0.000 < 0.05. Furthermore, the R² value of 0.670 indicates that interpersonal communication contributes 67% to the variation in client satisfaction. These results affirm that well-established interpersonal communication by Infrastructure Support personnel significantly enhances client satisfaction with the managed services provided by PT Profescipta WahanaTehnik.